2022
DOI: 10.3329/bpj.v25i2.60970
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Musculoskeletal Pain among Rural Handloom Weavers in Sirajganj, Bangladesh

Abstract: The loom industry is the traditional industry in Bangladesh. It is situated especially in rural areas. Many weavers are working in the handloom industry. The study aims to determine the prevalence rate of musculoskeletal pain and its associated factors. This study is a cross-sectional study, including openended and close-ended questionnaires. Two hundred fifty (250) handloom weavers have participated in this study. Frequency analysis and Chi-square test were done by R software. A total of 82.4% of weavers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Moonajilin et al (2020) conducted research among Savar residence, Bangladesh and reported that people (85%) who were more than 35 years old, conducted self-medication practice. Moreover, 54.7% middle aged (18-35 years) indigenous people were self-medicated in Chittagong hill tracts (Saha et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moonajilin et al (2020) conducted research among Savar residence, Bangladesh and reported that people (85%) who were more than 35 years old, conducted self-medication practice. Moreover, 54.7% middle aged (18-35 years) indigenous people were self-medicated in Chittagong hill tracts (Saha et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…As per our study, most of the married people practiced self-medication. 53.5% married indigenous people also self-medicated in Chittagong, Bangladesh (Saha et al, 2022). In Sri lanka, 60% married rural people perceived self-medication (Wijesinghe et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Common musculoskeletal problems include neck pain, limb discomfort, low back pain, joint pain, and chronic generalized pain. 1 Musculoskeletal disorders (MSDs) are injuries or disorders of the muscles, nerves, tendons, joints, cartilage, and disorders of the nerves, tendons, muscles and supporting structures of the upper and lower limbs, neck and lower back which are caused, precipitated or exacerbated by sudden exertion or prolonged exposure to physical factors such as repetition, force, vibration, or awkward posture. 2 Common symptoms include aching and stiffness, burning sensation in muscles, fatigue, muscle twitching, pain that worsens with movement, and sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%